If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6x + -32 = 2 Reorder the terms: -32 + -6x = 2 Solving -32 + -6x = 2 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -6x = 2 + 32 Combine like terms: -32 + 32 = 0 0 + -6x = 2 + 32 -6x = 2 + 32 Combine like terms: 2 + 32 = 34 -6x = 34 Divide each side by '-6'. x = -5.666666667 Simplifying x = -5.666666667
| 12=9x+3+6 | | p+1=16 | | 60x+75y=9 | | -8+n=-7 | | (-11)-w=(-36) | | 4x-3-7=-27 | | x-(-15)=10 | | 2y-20=35 | | 4x+7+2x=-5x | | -8(9k+7)=15+3k | | 6x-8x+10=9x+19+13 | | r+8=22 | | 5x+2(x-3)+2x=6x+3(x+2)-4+x | | x+y-24=0 | | 12m=240 | | -12x-2y=-54-3x | | Kx+13-8x=-1 | | -7d-2d=-33 | | -2x+3=.5x+3 | | 2x^2=7x-29 | | 17+a=8 | | 3x-7y=6-5y | | 20n=180 | | 1=X-2x^2 | | 3d=9d-9 | | 29-3c=9(7c+2) | | 6=7y+3 | | 6r-12=3+7r | | -20b=280 | | 345-4532x=12 | | 3y+2-4=6 | | 8x=16x+24 |